The application of notational analysis in futsal biomechanics research - Ismail, S. I.; Nunome, H. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: In 1998, the British Olympics Association (BOA) initiate its Performance Analysis Steering Groups where eff ort was made to bring together application of biomechanical and notational analysis to help improve the athletes` performance by understanding more about human movement relation to sports performance (Bartlett, 2001). Since then, it can be argued that the lack of co-utilization between both types of analysis in team sports performance has been acknowledged for quite some time now. On a diff erent note, biomechanical analysis on performance and footwear has received critique for not systematically reported the rationale of the analysed movement task in their research (Emery et al., 2016). Thus, the aim of this study was to use notational analysis to clarify the importance of selected futsal movements to be further analysed in footwear-related biomechanics research. Methods: A total of eight futsal matches from the 2014 ASEAN Futsal Championship (AFF Futsal Championship) were recorded and observed. The matches consist of four group stages, two semi-fi nals, a third-place play-off and the fi nal. These selections were made in order to obtain data from matches between the best performing teams and the team that fi nished last during group stages (n=4), and to compare them with matches among the best performing teams in the competition (semi-fi nals onwards, n=4). Based on the observation, eight movement indicators (forward translation, backward translation, side translation and slow rotation; defi ned as the low shoe-playing surface traction demand movement, and side step, crossover cut, fast rotation and sudden stop; defi ned as the high shoe-playing surface traction demand movement) were established. An independent sample t-test (p<0.05) was used to identify diff erences on the rate of occurrence of these movements in matches from diff erent stages during the tournament. Results: Based on the independent sample t-test results, it was found that there were signifi cant diff erences in occurrence of the two of the high-traction demand movements (crossover cut and fast rotation). No signifi cant diff erences were found for all low-traction demand movements when compared between the group stage matches and matches from semi-fi nals onwards. Conclusion: The rate of occurrence of high-traction demand movements tend to be higher in futsal matches among the best performing teams. Based on the study results, these movements were selected to be further analysed in biomechanical analysis on performance and footwear.